MENINGKATKAN KUALITAS MINDS-SKILL KONSELOR ISLAMI DENGAN MENJAGA KONDISI HATI - Ashari Mahfud; Diah Utaminingsih (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2018)
Counseling services are a process of assistance in order to assist individuals to find their way to goodness. The counselor as the organizer (subject) who provides assistance to the counselee in the form of counseling services, the gift is able to first bring himself first to goodness. The goodness is in relation to the people around, and their relationship with Allah SWT. To accompany counselees towards goodness, counselors need to have good expectancy, so that they can bring counselee thinking toward goodness. Good thinking skills, based on a good heart condition. Heart as the center of all elements of human beings. The heart must be maintained by various tips such as those delivered by Sunan Bonang (Islamic Ulama), namely; 1) reading the Qur'an and its meanings, 2) establishing night prayers (tahajjud) 3) gathering with pious people, 4) multiplying fasting 5) remembrance night.